1.34 µm picosecond self-mode-locked Nd:GdVO4 watt-level laser. (24th November 2016) - Han, Ming; Peng, Jiying; Li, Zuohan; Cao, Qiuyuan; Yuan, Ruixia
Abstract: With a simple linear configuration, a diode-pumped, self-mode-locked Nd:GdVO4 laser at 1.34 µ m is experimentally demonstrated for the first time. Based on the aberrationless theory of self-focusing and thermal lensing effect, through designing and optimizing the resonator, a pulse width as short as 9.1 ps is generated at a repetition rate of 2.0 GHz and the average output power is 2.51 W. The optical conversion efficiency and the slope efficiency for the stable mode-locked operation are approximately 16.7% and 19.2%, respectively.